NIGER DELTA CRISIS – A STUDY OF EVWEREM AND OTU- JEREMI COMMUNITIES: IMPLICATIONS FOR NIGERIA’S SUSTAINABLE DEVELOPMENT - Emma Chukwuemeka, Ph.D; Ngozi Ewuim, Ph.D; D.S.C. Amobi; Lizy Okechukwu, PhD (International Journal of Accounting Research, 2013)
The Niger Delta region constitutes a number of ethnic nationalities which are rich in natural resources mainly in oil and gas reserves. However, the region has suffered extreme marginalization and neglect over the years despite its major contribution to the nations economy leading to agitations for better living standards by the people. The agitations have transformed from peaceful talks and dialogue to violence, unrest and chaos resulting to huge losses to the region and affecting the development process of the nation at large. This study examined the effect of the Niger Delta crisis on Evwreni and Otu-jeremi communities in Delta State. Data was collected through the administration of questionnaires, conduct of interviews and consultation of books and relevant documents. The data analysed revealed that the Niger Delta crisis has affected job creation, infrastructure provision and maintenance as well as increased criminal activities in the areas. Finally, the researcher recommended diversification of the economy, job creation and training programmes, strenghtening of security measures, provision of basic amenities amongst others as a solution to the crisis in the region. Keywords: Crisis, Security, Development